Entrepreneurial learning in informal apprenticeship programs: Exploring the learning process of the Igbo Apprenticeship System (IAS) in Nigeria - Bridget Irene; Eunice Oluwakem Chukwuma-Nwuba; Joan Lockyer; Chioma Onoshakpor; Siona Ndeh (Cogent Business & Management, 2024)
This research examines the unique learning process of the Igbo Apprenticeship System (IAS). This approach to the development of enterprises and entrepreneurship, originated in the ethnic group of communities in the Southeastern part of Nigeria, uses mimetic learning to instil in its participants' knowledge and behaviours intended to create a lifelong approach and mindset to entrepreneurship development. This form of mimetic learning predates the mediaeval era and takes place outside the formal educational system. As a consequence, it largely does not rely on participants having a specific level of educational achievement. Rather it requires a long-term commitment from the apprentice, their family and the entrepreneur. The research expands the theoretical understanding of entrepreneurial learning through an evaluation of an entirely experiential base using the Mimetic Theory and Institutional Logics as the critical lens to explore the antecedents of entrepreneurial intention and social learning. It evaluates and combines the available evidence into a conceptual framework that shapes the process of entrepreneurial learning as an experiential activity. Qualitative data were gathered from 40 former and current apprentices and critically analysed using the illustrative case study and process tracing approach. The research contributes to the extant entrepreneurial learning process literature by identifying, reviewing and synthesizing available research into a conceptual framework that explores the process of entrepreneurial learning as an experiential process. It also highlights effective mechanisms of skills transfer and business training, contributing to the literature on informal/vocational training and human capital development. Key issues in entrepreneurship education including the different informal learning processes of the IAS and the identification of specific dynamics in the interaction and development of the learners were examined.
Keywords: 650; IAS; apprenticeships; mimetic learning; institutional logics